Potential effects of policy reform on the European Community sugar market and world sugar prices - Leuck, Dale (U.S. Department of Agriculture Washington, D.C.US, 1992)
Examines how alternative EC sugar policy reforms viz. the first is to allow for the sale and secondly the complete elimination of the EC sugar program. Analyzes these two policy alternatives with a simulation model of supply and utilization for the EC member countries linked to a world price equation.